Thermoelectric and Magnetic Properties of Pt-Substituted BaFe4-xPtxSb12 Compounds - GÜLER, ADİL (SPRINGER, 2017)
BaFe4-xPtxSb12 (x = 0, 0.1, 0.2) compounds were prepared by melting and annealing, followed by a spark plasma sintering method. Low-temperature thermoelectric and magnetic properties were investigated based on Seebeck coefficient, electrical and thermal conductivity and magnetization measurements. The structural properties of BaFe4-xPtxSb12 (x = 0, 0.1, 0.2) compounds were ascertained by powder x-ray diffraction analysis, confirming that all samples have a main phase of a skutterudite structure with the space group Im (3) over bar. The lattice parameters obtained, 9.202(5), 9.199(5) and 9.202(1) angstrom for x = 0, 0.1 and 0.2, respectively, were found consistent with literature. The Seebeck coefficient sign shows that holes are dominant carriers in all compounds. The local maximum Seebeck coefficient was observed around 50 K which may be a trace of paramagnon-drag effect of charge carriers. Thermal conductivity and electrical resistivity measurements were carried out between 4.2 K and 300 K. Temperature dependence of electrical resistivity reflects that all samples show semi-metallic behavior in our temperature range of 4.2-300 K. Samples for x = 0.1 and x = 0.2 show Kondo-like behavior. In magnetization measurement, we observe that there are two successive magnetic transitions in Pt-substituted compounds; however, there is only one (transition from a paramagnetic state to long-range magnetic ordering) in Pt-free compounds. In Pt-substituted compounds, the first transition appears at T-c = 48 K. In addition, the second transition is observed at T-irr = 30 K where an intermediate state is observed before the magnetic ordering transforms to an irreversible ferromagnetic state. We concluded that Pt substitution on the Fe side effectual on the thermoelectric and magnetic properties of BaFe4-xPtxSb12 (x = 0, 0.1, 0.2) compounds.
Keywords: Skutterudites; paramagnon drag effect; magnetization; thermo electric effect; SPIN FLUCTUATIONS; SR; CA; BA